Suatu Kajian Terhadap Tanggung Jawab Etis Pendeta Yang Berbisnis - Bella Priskila Mappadang; Wolter Weol; Arthur Gerung (Jurnal Ilmiah Wahana Pendidikan, 2022)
This article is a review of the ethical responsibilities of pastors in business. By using qualitative research methods on various literatures and using interview techniques to informants as supporting data that describes the life of pastors who do business in the east Manado IV region, the authors try to reveal that in order to be able to carry out their duties and responsibilities as a servant of God and have a side business or doing business, a pastor must have a solid understanding of how to understand Christian business in accordance with Christian ethics. There is nothing wrong with the pastor doing business, but the success of the ministry must also be prioritized. When a pastor wants to do business, then there must be some things in the ministry that must be sacrificed. As for this matter, it raises many views in the congregation later, both pros and cons. It turns out that doing two focuses is less able to make effectiveness in service..